Multiple simultaneous free flaps for head and neck reconstruction: A multi-institutional cohort. (January 2023) - Tharakan, Theresa; Marfowaa, Gifty; Akakpo, Kenneth; Jackson, Ryan; Zenga, Joseph; Puram, Sidharth V.; Pipkorn, Patrik
Highlights: Double free flaps are used for large, complex head and neck reconstruction. The most common free flap combination is fibula flap and anterolateral thigh flap. Operative time and microvascular success is comparable to single free flaps. Complications are common after multiple flaps, so careful patient selection is key. Abstract: Objectives: To describe the experience of two tertiary academic centers with multiple, simultaneous free flaps for complex head and neck defect reconstruction. Methods: Patients undergoing multiple, simultaneous free flaps from 2017 to 2022 were retrospectively reviewed. Results: Seventy-one patients (64.8% male, median age 61 years) were identified and underwent 143 free flaps. The leading surgical indication was squamous cell carcinoma (n = 48, 67.6%). Defect sites included oral cavity, maxilla, pharynx, parotid, skull base, and scalp. The most common free flap combinations were fibula (FFF) with anterolateral thigh flap (n = 33, 46.5%), radial forearm (RFFF) with scapula (n = 11, 15.5%), and RFFF with FFF (n = 10, 14.1%). Median operative time was 12 h. Median length of hospitalization was 10 days. At last follow-up (median 6 months), 141 flaps (98.6%) survived without partial nor complete flap failure. Conclusion: Multiple, simultaneous free flaps are a rare, yet reliable option for head and neck reconstruction in select patients with defects involving several tissue types, multiple functional areas, or large volumes.